Thomas Martinez as Philip Lombard, Katherine Sawyer as Vera Claythorne, and Ezra Dunklke-Polier as William Blore in 'And Then There Were None' (Tufts Archival Research Center, 2008)
Directed by Katie Welch. Production date was 2009-11-09.